PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS KETERAMPILAN PROSES SAINS PADA MATERI SISTEM SIRKULASI - Kharisma Diani; Renaldi Hermansyah; Rida Oktorida Khastini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
In the era of the COVID-19 pandemic, all teaching and learning activities were carried out online. Various difficulties faced by the teacher in delivering material in learning, especially in biology which there are science process skills. Therefore, this research was conducted to make a product and test the feasibility of a biology learning module based on science process skills on the circulatory system by collecting data in the form of a questionnaire. In this development research using ADDIE model. The result of the questionnaire on the analysis of media needs, material experts, and users, namely teachers and students, were analyzed quantitatively. Based on the result of the assessment by material expert and media expert that the biology learning module based on science process skills on the circulatory system material is valid. Then based on the assessment by practitional expert, the module is quite valid. Then based on the student response, it was found that the biology learning module based on science process skills on the circulatory system material is valid, feasible, and very interesting. Keywords: science process skills, learning module, circulatory system